Psikologi Kultural : Memahami Budaya Dalam Proses Kognitif Dan Emosi - Ulhaq, Dhiya; Muntaha Nour (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
Cultural psychology studies the influence of culture on individual cognitive and emotional processes, which is increasingly relevant in the era of globalization. Each culture has distinct values and norms, influencing how individuals think, feel, and behave. This study uses a qualitative descriptive approach through a literature review to explore the influence of culture on cognitive and emotional processes. A deep understanding of cultural psychology is crucial; by considering cultural differences in cognitive and emotional processes, educators can create more inclusive and effective learning environments. This research demonstrates that integrating cultural psychology into the educational curriculum can improve the learning outcomes of students from diverse cultural backgrounds.